2023
DOI: 10.1101/2023.10.10.561783
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A label-free approach for relative spatial quantitation of c-di-GMP in microbial biofilms

Catherine S. McCaughey,
Michael A. Trebino,
Allyson McAtamney
et al.

Abstract: Microbial biofilms represent an important lifestyle for bacteria and are dynamic three dimensional structures. Cyclic dimeric guanosine monophosphate (c-di-GMP) is a ubiquitous signaling molecule that is known to be tightly regulated with biofilm processes. While measurements of global levels of c-di-GMP have proven valuable towards understanding the genetic control of c-di-GMP production, there is a need for tools to observe the local changes of c-di-GMP production in biofilm processes. We have developed a la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…MALDI has already been applied for multiple microbiological applications, including bacterial imaging, providing novel insights into QS signalling, distribution, and metabolite quantification. (Feucherolles and Frache 2022;McCaughey et al 2023) Indeed, MALDI has been shown as a valuable technique to gain insight into QS pathways within biofilms, as it, for example, revealed the existence of an N-Acyl-homoserine lactone (AHL) QS system in Pseudomonas putida biofilms, coordinating bacterial cell density during biofilm maturation, and a relationship between biofilm development and spatial production of QS metabolites has been shown. (Pitchapa et al 2022) The AHL signalling involved in QS of gram-negative bacteria has been extensively studied due to the involvement in physiological activities of the biofilm, such as nutrient acquisition, conjugation and biofilm formation.…”
Section: Bacterial Biofilm Infections and Quorum Sensingmentioning
confidence: 99%
“…MALDI has already been applied for multiple microbiological applications, including bacterial imaging, providing novel insights into QS signalling, distribution, and metabolite quantification. (Feucherolles and Frache 2022;McCaughey et al 2023) Indeed, MALDI has been shown as a valuable technique to gain insight into QS pathways within biofilms, as it, for example, revealed the existence of an N-Acyl-homoserine lactone (AHL) QS system in Pseudomonas putida biofilms, coordinating bacterial cell density during biofilm maturation, and a relationship between biofilm development and spatial production of QS metabolites has been shown. (Pitchapa et al 2022) The AHL signalling involved in QS of gram-negative bacteria has been extensively studied due to the involvement in physiological activities of the biofilm, such as nutrient acquisition, conjugation and biofilm formation.…”
Section: Bacterial Biofilm Infections and Quorum Sensingmentioning
confidence: 99%